Large Cell Neuroendocrine Carcinoma of the Nasopharynx. Issue 6 (August 2015) - Dumars, Clotilde; Thebaud, Estelle; Joubert, Madeleine; Renaudin, Karine; Cariou-Patron, Gwenaëlle; Heymann, Marie-Françoise
<x xml:space="preserve">Abstract</x> Neuroendocrine tumors are rare, preferentially located in the gastrointestinal tract or in the lungs. We present the case of a 9-year-old child, presenting with a tissue mass involving the nasopharynx and associated with multiple pulmonary and bone metastases. The immunohistochemical analysis showed a proliferation of large tumor cells stained with Chromogranin A and Synaptophysin. The diagnosis of multimetastatic large cell neuroendocrine carcinoma was made. This tumor is infrequent in this location and particularly in children. This case describes the pathologic aspects and immunohistochemical results and presents a discussion of the differential diagnoses.